Teachers’ role in motivating EFL students at Palestinian Schools by using motivational strategies / Wafaa T. H. Juba, Ahmad Atawneh and Habibah Ismail - T. H. Juba, Wafaa; Atawneh, Ahmad; Ismail, Habibah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Cawangan Melaka, 2020)
This paper investigates the extent to which teachers motivate English as a Foreign Language (EFL) students at Palestinian schools and the strategies that they use to motivate students. It also discusses the meaning of motivation, the importance of motivation, and the different types of motivation. An attempt was made to answer the following questions: (1) To what extent do EFL teachers at Palestinian schools motivate their students? (2) What are the strategies that teachers use in order to motivate their students? The data were elicited through specially designed questionnaire and semi-structured interview. The problem of the study stems from the poor level of EFL students in language learning. Moreover, lack of studies conducted on English teachers in Palestine in the field of motivation leads the researcher to conduct this study. By examining the extent to which EFL teachers motivate their students at Palestinian schools, it was evident that 6.3 % of female teachers and 3% of male teachers do not motivate their students while 97% of male teachers and 93.7% of female teachers motivate their students by using verbal and non verbal motivation in order to attract them and to involve them in new topics. It was apparent that teachers can encourage students to become more active participants in the classroom by using different motivational strategies such as creating supportive learning atmosphere, using enjoyable games and activities, having good relationships with their students, and using interesting texts. However, the results reveal that some teachers encounter many difficulties in motivating their students. For example, 25% of female teachers and 14.3% of male teachers do not use technological or visual aids when introducing a difficult language task. The study recommends teachers to focus more on learners’ motivation and to use appropriate motivational strategies which help students to achieve better language learning.